The influence of the critical diffusion factors of 3D printing technology on the success of UAE construction Projects - FARIED, MANSOUR EBRAHIM DAOUD (2018)
3D printing applications in the construction industry have gained the interest of field specialists, especially in UAE. This is particularly because of the fact that the UAE Government has recently announced its target that at least twenty-five percent (25%) of the new buildings in Dubai should be utilizing the 3D printing technology by the year 2030. This research is aiming to identify the 3D printing technology’s critical diffusion factors influencing the success of the UAE’s construction projects. Through a critical review of the relevant literature, the study developed a framework based on the innovation diffusion theory developed by E.Rogers (Rogers, 2005); to identify critical factors leading to technology acceptance and, therefore, measuring the impact of those identified factors on the successful application of the technology in the UAE’s construction projects. The literature findings have been examined via a quantitative approach through a designed questionnaire and a subsequent data analysis via SPSS statistics software. The literature review identified thirty four factors classified under the five major attributes of technology diffusion following the innovation diffusion theory namely the relative advantage, the compatibility, the trail-ability, the complexity and the observability. All those thirty-four factors were found to be with an evident association with the level of successful implementation and success of the 3D printed project. The study suggests that the integration of all of these factors together will have a stronger level of influence and will lead to higher levels of application success. The study also suggests the classification of the relative advantage, compatibility and complexity as primary factors, and to classify the trial-ability & observability as secondary factors due to difference found in the level of influence that they have on the success of the project. The study faced a limitation on the availability of specific literature related to the 3D printing in construction in general, and in the UAE market in particular. Similar technologies and similar markets have, however, been taken as reference in areas for which precise information was not available. Finally, the study suggested a list of recommendations to be adopted by market stakeholders based on the research findings to facilitate the achievement of the government target.